Temporal shifts in phytoplankton communities in Cam Ranh Bay - Huynh, Thi Ngoc Duyen; Tran, Thi Minh Hue; Tran, Thi Le Van; Nguyen, Ngoc Lam; Doan, Nhu Hai (Vietnam Journal of Marine Science and Technology, 2025)
Phytoplankton communities can change rapidly in response to shifting environmental conditions. A dataset of phytoplankton and environmental factors in Cam Ranh Bay was analyzed to assess the temporal shifts in phytoplankton communities over both short-term (days, weeks) and long-term (seasons) periods. In this Bay, changes in phytoplankton compositions were insignificant found in short-term, while there was no clear pattern in abundance and biomass variation. Seasonally, significant changes in dominant phytoplankton were also observed, with dinoflagellates and diatoms predominating in the dry and wet seasons, respectively. Diatoms abundance and biomass were higher during the wet season, whereas dinoflagellate abundance was higher in the dry season. The dominant analysis revealed that some species prevailing throughout sampling periods, including Chaetoceros spp., Bacteriastrum sp., Coscinodiscus sp., Thalassionema frauenfeldii, Pleurosigma sp., and Protoperidinium spp. The pattern was clear seasonally, such as Chaetoceros diversus, Dictyocha fibula, and Tripos setaceus dominant in the dry season, and Guinardia striata, Leptocylindrus danicus, and Chaetoceros compressus in the wet season. Multidimensional scaling statistical analysis (NMDS) indicated both nitrate and nitrite impact on a diatom group, Bacillariophyceae, during the dry season, while other diatom groups, Mediophyceae, with phosphate and ammonium and Coscinodiscophyceae with temperature. In the wet season, Bacillariophyceae were closely related to nitrite, nitrate, and phosphate, whereas Mediophyceae were associated with ammonium and DIN. The density of Dinophyceae was inversely related to silicate, salinity, and fluorescence. Our results provide insights into how and which types of nutrients and temperature and salinity variations, influence the rapid changes in phytoplankton communities within coastal tropical embayment.